Adult-onset Still’s disease: A disease at the crossroad of innate immunity and autoimmunity - Rao, Shijia; Tsang, Lemuel Shui-Lun; Zhao, Ming; Shi, Wei; Lu, Qianjin (Frontiers in Medicine, 2022)
Adult-onset still’s disease (AOSD) is a rare disease affecting multiple systems and organs with unknown etiology, the clinical symptoms and laboratory indicators are not specific. According to those unspecific clinical presentations and laboratory findings, infection, tumor, connective tissue disease and other diseases must be ruled out before diagnosis. The diagnosis of AOSD is a great challenge for clinicians. The mechanism of AOSD pathogenesis is complicated and still being studied. Tranditionally, AOSD is considered as an autoinflammatory disease by the strong activation of innate immune system. Recently, several evidences indicate that adaptive immunity is also involved in the pathogenesis of AOSD. Increased α-soluble receptor of IL-2 may suggest T cell activation and proliferation in AOSD patients. Increased IL-4 and IFN-γ producing T cells were found in active AOSD and related to disease severity. Frequencies of Treg cells in AOSD were significantly lower and were inversely correlated with disease severity. According to these, more and more researchers have reached a consensus that AOSD is a disease at the crossroads of innate immunity and autoimmunity. In this review, we will provide a comprehensive insight into AOSD, detailed describing the lasted research progress and the immunological mechanism contribute to the disease. At the meantime, different treatment options and the efficacy and safety of various biologic agents are also discussed. A further understanding of AOSD requires closer cooperation among doctors from different department, and this review will provide a new idea for diagnosis and therapeutic options.